The Antichrist and His Plot Against Russia: Conspiracy Theories and Eschatology - Magda Dolińska-Rydzek (Colloquia Humanistica, 2022)
In post-Soviet Russia, there is a relatively widespread conviction that events such as the Bolshevik Revolution, World War II, and the collapse of the Soviet Union were not the results of historical contingency but of a complex vicious plot exercised by some evil forces aiming to destroy Russia. Depending on political needs, the enemy plotting against Russia has the face of a Jew, Muslim, Freemason, oligarch, or liberal, operating both from outside and inside of the country. Interestingly, many conservatives and religious fundamentalists seem to believe that the plot against Russia is orchestrated not by human agents but by the embodiment of all evil and the herald of the end of the world – the Antichrist. In my paper, I will address these beliefs and discuss the proximity between conspiracy theories and eschatological discourses. Referring to the literal meaning of the Greek word apokalypsis (to disclose, to unveil), I will attempt to explain the role of apocalyptic and conspiratorial narratives that offer to reveal the hidden reality behind what ordinary people can see. Also, I will demonstrate their implications in the broader context of the public discourse in contemporary Russia.